The Utilization of Whole Cotton Seed as a Substitute in Diets on General Physiological Changes, Animal Welfare Behavior and Productivity of Fattening Beef Cattle in Thailand - Umpapol, Hanchai; Jitrajak, Tharadol; Songvicha, Choompol; Tantisirin, Pannapa; Hanmontree, Reungrit; Sripandon, Jesda; Umpapol, Sumontip (Pakistan Journal of Nutrition, 2011)
This experiment was conducted to study on general physiological changes, animal welfare behavior and productivity of Whole Cotton Seed (WCS) substitute in diets for Pon-Yang-Kham fattening beef cattle production. All cattle were uniform in body condition score in each group and were raised under the management of small holders in Pon-Yang-Kham co-operative, Sakon-Nakhon. Sixteen cattle were allocated in Randomized Complete Block Design (RCBD) with 4 diets. Diet 1 was WCS substitute 0 percentage, diet 2 was 5 percentages of WCS, diet 3 was 10 percentages of WCS and diet 4 was 15 percentages of WCS. The environment effects and blood samples were collected and analyzed for examining the cortisol concentration level by RIA technique. General physiological, hematological changes, animal welfare behavior and productive performance were recorded for the entire period of experiment. The result showed that Temperature Humidity Index (THI) effected on the increasing of general physiological changes, Heat Tolerance Co-efficient (HTC), sweating rate, hematology, cortisol concentration and activities of animal welfare behavior with highly significant differences (p<0.01). The statistical analysis showed that the productive performance, carcass quality and beef marbling of carcass of the fattening Charolais crossbred cattle were significant differences (p<0.05).